SYNTHESIS AND CHARACTERIZATION OF METAL PHTHLOCYANINE COMPLEX USING CIPROFLOXACIN-SUBSTITUTED LIGAND - Dauda, Aminu; Mahmoud, Auwal A.; Adamu, H. M.; Olaleye, Abdul Ademola; Suleiman, A. K. (FUDMA JOURNAL OF SCIENCES, 2023)
In this research work, two metal complexes were synthesized from the prepared 4-nitrophthalonitrile ligand. It began with the cyclotetramerization of 4-(ciproxy) phthalonitrile in the presence of metals salt (cobalt and copper), which gave substituted metal phthalocyanine complexes. The formation of the synthesized compounds was confirmed by FT-IR spectrophotometry, Thermogravimetric Analyzer (TGA) and UV-VIS spectrophotometry. At a heating rate of 10 oC min-1, TGA was conducted under Argon using a SHIMADZU Thermogravimetric Analyzer TGA-50 Instruments. Solubility of the compounds was confirmed in some common laboratory solvents (acetone, methanol, and DMF). The electronic spectra of copper phthalocyanine compound (CuPc) in DMF, showed intense Q absorption at 690 nm, the Q band absorption was observed at 678 nm for cobalt phthalocyanine (Copc). TGA results of the thermal stability of the phthalocyanine derivatives, when the phthalocyanine was heated up to 700 oC to determine the degradation temperature, showed that the phthalocyanines began to lose weight at 300 oC and 309 oC for Co and Cu phthalocyanine respectively. Therefore, it could be concluded that the synthesis of metal phthalocyanines complex using antibiotic as substituent was achieved and the complex synthesized in this study showed suitably high thermal stability.
Keywords: Ciprofloxacin; Phthalocyanine; Metal Complex; Ligand